Glycogen Synthase Kinase 3β Is a Negative Regulator of Growth Factor-induced Activation of the c-Jun N-terminal Kinase() - Liu, Shuying (J Biol Chem, 2004)
The c-Jun N-terminal kinase (JNK)/stress activated protein kinase is preferentially activated by stress stimuli. Growth factors, particularly ligands for G protein-coupled receptors, usually induce only modest JNK activation, although they may trigger marked activation of the related extracellular signal-regulated kinase. In the present study, we demonstrated that homozygous disruption of glycogen synthase kinase 3β (GSK-3β) dramatically sensitized mouse embryonic fibroblasts (MEFs) to JNK activation induced by lysophosphatidic acid (LPA) and sphingosine-1-phosphate, two prototype ligands for G protein-coupled receptors. To a lesser degree, a lack of GSK-3β also potentiated JNK activation in response to epidermal growth factor. In contrast, the absence of GSK-3β decreased UV light-induced JNK activation. The increased JNK activation induced by LPA in GSK-3β null MEFs was insufficient to trigger apoptotic cell death or growth inhibition. Instead, the increased JNK activation observed in GSK-3β−/− MEFs was associated with an increased proliferative response to LPA, which was reduced by the inhibition of JNK. Ectopic expression of GSK-3β in GSK-3β-negative MEFs restrained LPA-triggered JNK phosphorylation and induced a concomitant decrease in the mitogenic response to LPA compatible with GSK-3β through the inhibition of JNK activation, thus limiting LPA-induced cell proliferation. Mutation analysis indicated that GSK-3β kinase activity was required for GSK-3β to optimally inhibit LPA-stimulated JNK activation. Thus GSK-3β serves as a physiological switch to specifically repress JNK activation in response to LPA, sphingosine-1-phosphate, or the epidermal growth factor. These results reveal a novel role for GSK-3β in signal transduction and cellular responses to growth factors.